Efeito do jogo senha em funções executivas - Joana D'arc Assunção Nogueira de Oliveira (2018)
Board games are often used as a pedagogical resource for the purpose of training and developing executive functions and improving school performance. Research and educational programs with password games suggest that experience with this kind of game helps improve player performance and that this training would be appropriate for developing deductive reasoning. We conducted a 10-week program with 42 elementary students in which a group of 19 children played Mastermind for 1h weekly while the other group took classes on Neurosciences for the same period of time. Participants were assessed before and after the program. We used the testes Tower of London, Digit Span, Corsi Cubes, Posner and the Victoria version of Stroop to evaluate executive functions. An ANOVA showed a marginally significant interaction for the planning task. The group that played Mastermind got a better performance than the group that did not play in the Tower of London test. This result is consistent with previous works on the effect of training with this game on problem-solving tasks that require mental planning. In work memory tasks, inhibitory control and attention there is no evidence of any effect resulting from the program. After 10 weeks of regular school play, participants also showed improvement in game performance. Nevertheless, they remained inefficient in the tasks in which the use of deductive reasoning was necessary. The low number of correct answers in these tasks is in agreement with previous researches that demonstrate that to go better in the game Mastermind does not necessarily imply greater competence in the use of the deductive reasoning. However, it could be an appropriate tool for improving mental planning skills in problem solving.